Evaluasi Kinerja Waralaba Olahan Ayam dengan Rantai Pasok Tersentralisasi dan Terdesentralisasi di Kota Malang - Sucipto Sucipto; Andriana Wihartantri Kusumaningrum; Danang Triagus Setiawan (JURNAL TEKNIK INDUSTRI, 2018)
At present the supply of raw material for the franchise is centralized from the franchise center, while the decentralized franchise is the responsibility of the outlet. This will have an influence on supply chain performance and guarantee of halal franchise business. This study aims to compare franchise performance with a centralized and decentralized supply chain in implementing the Halal Assurance System (SJH). The object of the research is 2 fried chicken processed franchises in Malang City. The study used qualitative and quantitative descriptive analysis methods. Retrieval of data through interviews, observation, and document analysis. The theoretical framework using SJH LPPOM MUI, the Tieman supply chain halal guarantee framework and the Frazelle supply chain performance efficiency framework model. The results of the research show that the halal guarantee of the second supply chain of the franchise has fulfilled the SJP LPPOM MUI, but it is not fully in line with the more detailed guarantee of the Tieman supply chain. Centralized franchise supply chain performance PT. X is more efficient on indicators of approximate accuracy, emergency purchase presentations, total shipping costs, and the cost of the entire warehouse. Decentralized franchise supply chain performance PT. Y is more efficient on purchasing lead time indicators, ordering costs, on time delivery, average delivery time, and order entry time. The two franchises have the same supply chain performance on the order suitability indicator, the percentage of materials sent either, the level of accuracy of inventory, wasted stock damaged, and the value of stock of unused items. Overall, centralized franchises are better than decentralized franchises associated with HAS implementation and supply chain performance to gain consumer trust.